Peningkatan Kecepatan Efektif Membaca Siswa dengan Menggunakan Metode Klos - Sihombing, Novita Asmi (GERAM: Gerakan Aktif Menulis, 2023)
This research was conducted due to the low reading proficiency of students in school. The implementation of the Klos method in reading instruction is an effort to address this issue. The objective of this study is to enhance the effective reading speed of students in Grade XI IPA1 at SMA Negeri 3 Bangko Pusako by utilizing the Klos method. The research involved a sample of 32 students throughout three instructional cycles. The data analysis technique used was qualitative analysis, applied to qualitative data obtained from observations of students and teachers during classroom instruction. Quantitative analysis was conducted on the results of the students' effective reading speed test using the Klos method. In the first cycle, the reading comprehension was still considerably low with an average of 85.54 words per minute (wpm), an independent level of 81.25%, an instructional level of 40.61%, and a frustration level of 40.62%. In the second cycle, positive changes were observed, with the average effective reading speed reaching 156.88 wpm. The independent level achieved was 71.87%, the instructional level was 6.25%, and the frustration level was 9.37%. In the third cycle, the average effective reading speed further increased to 204.02 wpm, reaching a 100% independent level. The analysis results demonstrate that students' effective reading speed can be improved with the assistance of rapid reading activities taught using the Klos method.